Tempo despendido durante 12 semanas de treinamento e desempenho tático-técnico no voleibol escolar - Grisi, Raianne de Brito (2019)
The objective of the study was to compare the training time of volleyball motor skills spent during 12 weeks in school teams. Moreover, a secondary purpose was comparing performance indicators during a competition. This is a research with a longitudinal design. The training of five teams was followed for 12 weeks, its actions being registered in chips, and 16 games of the championship of Paraíba were filmed. Anova one-way identified differences between the teams as regards the time spent and in the performance indicators between the teams classified according to the position in the competition ranking. We can conclude that the time spent in training is fundamental for the performance during the competition.